Euro-Par 2015 : Parallel Processing Workshops : Euro-Par 2015 International Workshops, Vienna, Austria, August 24-25, 2015, Revised selected papers /: Parallel Processing Workshops : Euro-Par 2015 International Workshops, Vienna, Austria, August 24-25, 2015, Revised selected papers. (2015) - Unknown
No abstract available